TRANSFORMASI NILAI_NILAI HUMANISME RELIGIUS DI ERA DIGITAL(Studi Kritis Praktik Pendidikan di Sekolah dan Madrasah) - Suripto; Mohammad Riza Zainuddin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine in depth the integration of religious humanism values in digital learning within schools and madrasahs, focusing on the process of meaning transformation experienced by teachers and students. The development of educational technology offers both opportunities and challenges for Islamic education, where religious humanism combining respect for human dignity with spiritual dimensions needs to be systematically embedded in digital learning practices. Transformative Learning theory serves as the primary analytical framework, while Care Ethics and al-Attas's ta'dib concept reinforce the affective, moral, and spiritual aspects. This research employed a qualitative approach with a multi-site case study design in three schools and two madrasahs in Tulungagung, East Java. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed through reduction, categorization, and theory driven interpretation. The study identified five key findings: (1) shared understanding of religious humanism, (2) value-based digital learning strategies, (3) institutional policy support, (4) integration of values into daily practices, and (5) technical, pedagogical, and cultural challenges addressed through adaptive strategies such as teacher training and digital module development. The resulting conceptual model integrates the primary and supporting theories in a synergistic relationship. The integration of religious humanism values in digital learning has been proven to foster profound meaning transformation, strengthen teacher-student relationships, and enhance the moral and spiritual dimensions of Islamic education, thereby contributing theoretically to contemporary Islamic education development and offering practical guidance for educators and policymakers.